Studi Karakteristik Suhu Permukaan Laut (SPL) Di Perairan Selat Lombok Menggunakan Citra Satelit EOS Aqua MODIS - Prima, Fitra Cahya; Astawa Karang, I Wayan Gede; Hendrawan, I Gede (Journal of Marine Research and Technology, 2021)
The Lombok Strait is a strait located between Lombok Island and Bali Island which connects the waters of the Bali Sea to the Indian Ocean, whose SST conditions vary with oceanographic-atmospheric conditions in the Indian Ocean and the Pacific Ocean. This research aims to determine the temporal and spatial SST in the North and South Lombok Strait. Therefore, this study divides the Lombok Strait area into two because of the influence of the Pacific Ocean and the Indian Ocean. The method used in this research is descriptive and statistical analysis. The highest average monthly SST in the northern and southern Lombok Strait occurred in April at 29.11 °C and the lowest in August at 26.82°C. For the average seasonal SST, the highest occurred at transition I of 28.86°C, and the lowest occurred in the eastern season at 27.39°C. The highest average annual SST occurred in 2010 at 28.83°C and the lowest occurred in 2018 at 27.69°C. The northern SST anomaly has the same fluctuation as ENSO with inversely proportional IOD. Southern SST anomaly has fluctuation which is inversely proportional to ENSO and IOD. The correlation between SST anomaly in the north and ENSO correlates 0.90 (very strong), while with IOD it correlates 0.12 (very low). The correlation between SST anomaly in the southern part and ENSO correlates -0.11 (very low), while with IOD it correlates -0.73 (strong)